Flood Susceptibility Mapping of Brebes Region Using Multi-Source Geospatial Data and Analytical Hierarchy Process (AHP) - Restianto, Mohammad Obie; Poniman, Aris; Supriyatno, Makmur (Proceeding International Conference on Religion, Science and Education, 2024)
Floods are the most frequent natural disasters in Indonesia. Brebes Regency is periodically threatened by flood disasters. With this disaster, flood susceptibility mapping is needed. This research uses the Analytical Hierarchy Process (AHP) weighting method and using multi-source geospatial data. There are 10 parameters used in this research: Topographic Wetness Index, Elevation, Slope, Precipitation, LULC, NDVI, Distance from river, Distance from road, Drainage density, and soil type. The results of this research show that Brebes Regency has a high flood susceptibility is 3.3%, moderate flood susceptibility is 46.39%, low flood susceptibility is 50.03%, and very low flood susceptibility is 0.23%.